Subclavian arterial injury associated with clavicle fracture - Tanmit , Parichat; Angkasith, Phati; Teeratakulpisarn, Panu; Wongkonkitsin, Narongchai; Prasertcharoensuk, Supatcha; Thanapaisal, Chaiyut (Asia-Pacific Journal of Science and Technology, 2024)
Reports on clavicle fractures with subclavian artery injury have been rare. Damage to vessels may result in threatening limb perfusion and potentially devastating hemorrhage. There should be an accurate diagnosis in order to prevent delays in management and subsequent complications. This research aimed to evaluate the pattern of subclavian artery damage due to the clavicle fracture. A 10-year retrospective analysis from a level one trauma center between 2012 and 2021. We treated 1054 cases with clavicle fractures. The frequency of subclavian arterial injury associated with clavicle fracture was 0.85%. Our data’s findings revealed typical clinical indicators that signify subclavian artery injury. Most patients initially had ischemic symptoms (77.8%). The most common type of injury (71.42%) was the Allman’s classification group I fracture or midshaft fracture with displacement. The common associated lesions were brachial plexus injuries (100%), rib fracture (66.66%), pneumohemothorax (44.44%), and scapular fracture (44.44%). As a minimally invasive therapeutic option, endovascular management is a good substitute for traditional surgical procedures. A high index of clinical suspicion combined with the correlation of associated physical findings is the primary diagnosis for subclavian arterial injury.